The Influence of Supervision, Coordination, Work Attitudes, Work Skills, and Empowerment on Work Productivity of UMKM Tahu Tempe Employees in Semarang City - Dherex Fajar Maulana; Sutrisno; Noni Setyorani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of Supervision, Coordination, Work Attitude, Work Skills, and Empowerment on Work Productivity of UMKM Tahu Tempe Employees in Kotap Semarang. The research population is all employees of UKM Tahu Tempe in Semarang City, the sample that has been determined in this study is 385 employees using a non-probability sampling technique with the convenience sampling method using the PCochran formula. Data analysis in this study used multiple linear regression analysis of the SPSS version 24 program. The results of the analysis and discussion show that partially Supervision has a positive and significant effect on Work Productivity, that partially Coordination has a positive and significant effect on Work Productivity, partially Work Attitude has a positive and significant effect on Work Productivity, partially Skills Work has a positive and significant effect on Work Productivity, partially Empowerment has a positive and significant effect on Work Productivity, Supervision, Coordination, Work Attitude, Work Skills, and Empowerment simultaneously has a positive and significant effect on Work Productivity of UMKM Tahu Tempe Employees in Kota Semarang